1997
DOI: 10.1037/0021-843x.106.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurophysiological evidence for altered processing of anxiety-related words in panic disorder.

Abstract: Body-related and nonsomatic words were presented tachistoscopically to 15 panic patients and 15 healthy controls at each participant's threshold for correctly identifying 50% of neutral words. Behavioral (proportion of words correctly recognized) and electrocortical (event-related brain potentials [ERPs]) measures were registered. Panic patients recognized more body-related than nonsomatic words, and body-related as compared with nonsomatic words elicited, in these patients, significantly larger P300 amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 25 publications
5
66
2
1
Order By: Relevance
“…Furthermore, higher amplitudes for the N2 and P2 and partially the P1 component triggered by startle probes during viewing of affective pictures were reported (Schupp, Cuthbert, Bradley, Birbaumer, & Lang, 1997), as well as an N1 effect depending on picture content (Keil et al, 2002). Finally, Gardner, Cacioppo, Crites, and Berntson (1994) as well as Pauli et al (1997) presented evidence that disorder-relevant stimuli elicit larger PSWs in phobic or panic patients, respectively, than in healthy control participants. In sum, there is evidence for a facilitated early processing of emotional stimuli reflected in earlier components of the ERP (e.g., N1, and P2) and for a deeper conscious evaluation of emotional stimuli reflected in later components (e.g., PSW).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, higher amplitudes for the N2 and P2 and partially the P1 component triggered by startle probes during viewing of affective pictures were reported (Schupp, Cuthbert, Bradley, Birbaumer, & Lang, 1997), as well as an N1 effect depending on picture content (Keil et al, 2002). Finally, Gardner, Cacioppo, Crites, and Berntson (1994) as well as Pauli et al (1997) presented evidence that disorder-relevant stimuli elicit larger PSWs in phobic or panic patients, respectively, than in healthy control participants. In sum, there is evidence for a facilitated early processing of emotional stimuli reflected in earlier components of the ERP (e.g., N1, and P2) and for a deeper conscious evaluation of emotional stimuli reflected in later components (e.g., PSW).…”
mentioning
confidence: 95%
“…While the former can be interpreted as a heightened physiological arousal triggered by FR stimuli, the latter presumably reflects a match between participants' responses to FR stimuli and aversive outcomes (De Jong et al, 1995), and this match may promote a covariation bias (Tomarken et al, 1995). Other physiological measures which were successfully used to characterize emotional responses associated with the processing of affective stimuli are the acoustic startle response (ASR) (e.g., Pauli, Diedrich, & Müller, 2002) and event-related brain potentials (ERPs) (e.g., Amrhein, Pauli, Mühlberger, & Wiedemann, 2004;Pauli et al, 1997). Both measures may offer additional information about the mechanisms underlying covariation bias.…”
mentioning
confidence: 99%
“…These questions make even more sense when an increased attentional bias is present, i.e., if the task involves emotional processing, such as in exposure to faces or words that are reminiscent of the disorder. 5,12,[17][18][19][20][21] Another question concerns the possible relationship between a decrease in processing speed and a change in executive functions. This question stems from one study, which hypothesized that differences in this area in one group of patients could be a result of the group itself being more prone to difficulty in behavioral strategies.…”
Section: Discussionmentioning
confidence: 99%
“…19 The other two articles used neutral words and words related to the disorder; in both studies, PD patients showed an attentional bias for information related to the disorder. 20,21 One of the studies compared patients with PD (n=15) to a control group (n=15), 20 and the other study compared patients with OCD (n=18), patients with PD (n=15), patients with hypochondriasis (n=14) and a control group (n=19). 21 …”
Section: Affective Processing Of Faces and Wordsmentioning
confidence: 99%
“…Patients did evidence an emotionally dependent recognition bias later in processing (> 1 OOOms) over frontocentral sites, however, suggesting that they may "compensate for their automatic processing deficits with slow, capacity-limited, and consciously controlled strategies, which are reflected in the very late part of the ERP waveform" (p. 367). Pauli et al (1997) also utilized a task that manipulated the emotional valence of words, visually presenting 15 panic disord~r patients and 15 controls with words that were either somatic or non-somatic in nature. The stimuli were presented tachistoscopically at each individual's perception threshold, while ERPs were recorded from four left, four right, and three midline electrodes.…”
Section: Defining Event Related Potentialsmentioning
confidence: 99%